Influence of demodex mites on life quality of patients with acne and rosacea - Anzhela Kravchenko (Universitas Indonesia, 2019)
Background: Dermatology life quality index (DLQI) is the objective tool for the evaluation of the impact of dermato-venereological diseases on people's lives. The article assessed DLQI in patients with acne and rosacea, with and without Demodex mites. Methods: 60 patients with acne and rosacea were observed and divided into two equal groups (30 patients each) depending on the presence of the Demodex mites. All patients completed a DLQI questionnaire. Results: DLQI score of patients of group I (with the presence of the Demodex mites) have a very strong effect of the diseases on a patient's life, whereas in group II the diseases affect moderately. Quality of life of patients in group I varied depending on the type of Demodex mites species. Discussion: It was revealed that Demodex folliculorum brevis had a moderate effect on the life of patients, while in the presence of Demodex folliculorum diseases affect greatly on the patient`s life. Conclusion: In the course of the study, it was revealed that the Demodex mites aggravated the self-perception of patients with acne and rosacea.